Analysis of Educational Tourism Services - Madina, Ibragimova (European Journal of Life Safety and Stability (2660-9630), 2023)
This article reflects the ways to use educational tourism in the transformation of tourism into a strategic sector of the economy in our country, educational tourism is a rapidly developing sector of the tourism economy, recognized around the world. It also provides an analysis of educational tourism services around the world. The author highlights the penetration of the processes of globalization of international relations in Uzbekistan, the development of two sectors - education and tourism in a harmonious, interdependent relationship and the possibility of obtaining appropriate benefits from this relationship.